2006
DOI: 10.1177/155005940603700105
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Alpha Power Asymmetry in Aggressive Children and Adolescents with Mood and Disruptive Behavior Disorders

Abstract: Building on prior research, which has suggested a relationship between aggression and left frontal activity, our study tested the hypothesis that proneness to impulsive aggression would be related to relative left frontal overactivation. EEG one-hertz resting alpha power frontal asymmetry was examined in 65 pediatric male psychiatric patients with a history of impulsive aggression and comorbid mood and disruptive behavior disorders. The strongest finding, which emerged from this analysis, was a finding of rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 37 publications
3
32
1
Order By: Relevance
“…This pattern was later conceptually replicated by Hewig, Hagemann, Seifert, Naumann, and Bartussek (2004) and by Rybak, Crayton, Young, Herba, and Konopka (2006). Harmon-Jones (2004) later confirmed that this pattern is not attributable to any positive feelings about anger among people high in trait anger.…”
Section: Hemispheric Activation Affect and Motivational Directionmentioning
confidence: 64%
“…This pattern was later conceptually replicated by Hewig, Hagemann, Seifert, Naumann, and Bartussek (2004) and by Rybak, Crayton, Young, Herba, and Konopka (2006). Harmon-Jones (2004) later confirmed that this pattern is not attributable to any positive feelings about anger among people high in trait anger.…”
Section: Hemispheric Activation Affect and Motivational Directionmentioning
confidence: 64%
“…In addition, a subset of this sample was comprised of adolescents in a psychiatric inpatient unit for impulsive aggression. Even among these individuals, trait anger related positively with greater left than right frontal activity (see also, Rybak, Crayton, Young, Herba, & Konopka, 2006). Asymmetrical activity in other regions did not relate with anger.…”
Section: Trait Angermentioning
confidence: 93%
“…For social and personality research, incongruent alpha band activation between the left and right hemispheres of the brain reveal patterns related to motivational direction (Rybak, Crayton, Young, Herba, & Konopka, 2006;Gable & HarmonJones, 2008). Motivation is described as the "energization (i.e., instigation) and direction of behavior (Elliot & Covington, 2001, pp.…”
Section: Social Neurosciencementioning
confidence: 99%
“…For example, approachrelated emotions such as anger and aggression tend to show greater left prefrontal hemispheric activation over right in the infant, adolescent, and adult brain (Harmon-Jones & Sigelman, 2001;Rybak et al, 2006). Emotion-related approach motivation like anger have adaptive functions, in some cases inhibiting fear and increasing one's confidence, possibly contributing energy to act towards some action (i.e., approach motivation) (Harmon-Jones & Allen, 1998).…”
Section: Social Neurosciencementioning
confidence: 99%